KONSEP AL HIKMAH DALAM FILSAFAT MULLA SADRA - Nur Khosiah (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2020)
Mulla Sadra had the full name of Shadr Al-Din Muhammad Ibn Ibrahim Ibn Yahya Qawami Al-Syirazi. He was born in 1572 A.D. in Syiraz. From the relatively long Mulla Sadra's life of approximately seventy years, it can be divided into three different periods. First, the childhood and school periods in Syiraz and Isfahan. Secondly, the period of asceticism near Qum and the third, the teaching and writing period that presented the results and the fruits of the two previous periods. In his major work al-Hikmah al-Muta'aliyah fi al-Asfar al-Aqliyah al-Arba'ah, Sadra outlines the whole issue of Islamic philosophy, of the nature of God, the nature of the universe and the fate of mankind. One of the important and interesting of Sadra is his view of the movement of the Subatansi (al-Harakah al-Jauhariyah) that speaks of the occurrence of changes in the form of the universe.